Geometrically uniform hyperbolic codes - Lazari, Henrique [UNESP] (2005)
In this paper we generalize the concept of geometrically uniform codes, formerly employed in Euclidean spaces, to hyperbolic spaces. We also show a characterization of generalized coset codes through the concept of G-linear codes.